Influence of winter rations upon returns from wintering, grazing and full feeding yearling steers. - Weber, A.D. (Kansas Agricultural Experiment Station, 2012)
The primary purpose of this experiment was to test the value of prairie hay in a ration for wintering yearling steers. The quantity of prairie hay available for cattle feeding in Kansas has increased greatly in recent years due to the declining horse population. Because of this trend, it is planned to continue these studies of prairie hay for several years to determine how it can be used to the best advantage.
Keywords: Beef; Winter rations; Yearling steers; Prairie hay; Cattle performance